Application of Green Nanocomposite to Adsorb Cadmium ion in Wastewater - Thu Ha, Hoang; Dinh Minh, Tran; Minh Nguyet, Ha (VNU Journal of Science: Earth and Environmental Sciences, 2021)
In the condition of industrialization, the water environment has been contaminated by industrial and agricultural waste as well as pharmaceutical residuals. These sources of waste water are usually treated efficiently prior to releasing into environment. This leads to a significant quantity of pollutants accumulated in water, threating seriously to human health. Among various detected pollutants, Cadmium and its compounds are considered as one of the most dangerous reagents. They can be released to the environment from different sources of waste, such as metal, alloy and metal plating, and Cd-Ni batteries, which clearly showed a danger to the human health. This work aims to develop a novel “green” material applied for highly efficient treatment of Cd (II). The concept “Green material” indicates the material which is composed of environmental-friendly compounds (non-toxic to human and organisms, degradable or biodegradable). The novel material C 2 H 5 OH-SiO 2 /PANI (CSP) was synthesized using two-step procedure including functionalization of silicon oxide nanoparticles (SiO 2 ) by polyaniline polymer (PANI) and dispersion of SiO 2 /PANI  in ethanol under ultrasound sonication. All components of CSP including Silica, ethanol, PANI do not have negative effect on environment, thus they are applied in plenty of fields. CSP were successfully synthesized and characterized by several methods and techniques such as FTIR, SEM, TEM and BET analysis. Based on the practical data, the Cd (II) adsorption was followed by Langmuir adsorption isotherms, and the pseudo-second order adsorption kinetic. CSP has obtained the Cd (II) maximum adsorption capacity of 301.23 mgg -1 , which is higher than the previous reported adsorbents. Cd (II) adsorption by CSP is desired at pH 6, reaction time of 150 min, initial concentration of Cd (II) as 300 mgL -1 , CSP weight as 0.6 g. Adsorption data show that pH is one of the most important factor in Cd (II) adsorption due to the formation of surface complexes between Cd (II) and the functional groups of CSP such as hydroxyl group (OH - ), silanol (Si-OH), amine (–NH 2 ), quinoid imine [C=N–] and benzenoid amine [–NH–].